The American Revolution [videorecording (DVD)] - Ward, Geoffrey C.; Coyote, Peter; Brolin, Josh; Branagh, Kenneth; Danes, Claire, 1979-; Dancy, Hugh, 1975-; Schreiber, Liev; Menzies, Tobias, 1974-; Rhys, Matthew, 1974-; Hanks, Tom; Arkin, Adam; Lewis, Damian, 1971-; et al. (PBS, 2025)
The American Revolution was at once a war for independence, a war of conquest, a civil war, and a world war, fought by neighbors on American farms and between global powers an ocean or more away. It impacted millions from Vermont's Green Mountains to the swamps of South Carolina, from Indian Country to the Iberian Peninsula. In defeating the British Empire and giving birth to a new nation, the American Revolution turned the world upside-down. Thirteen colonies on the Atlantic Coast united in rebellion, won their independence, and established a republic that still endures.The American Revolution, our six-part, twelve-hour series on America's founding struggle, will present the story of the men and women of the Revolutionary generation, their humanity in victory and defeat, and the crisis that they lived through. By weaving together accounts of American political leaders and their British counterparts with the perspectives of the so-called ordinary people who waged and witnessed war, The American Revolution will be an expansive, evenhanded look at the virtues and the contradictions in the fight for independence and the birth of the United States.